Glosa do wyroku Naczelnego Sądu Administracyjnego z dnia 6 czerwca 2013 r., II FSK 2026/11 - Drelichowska, Angelika (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The author accepts as amatter of principle the thesis of the commented judgement concerning lack of adebtor of the attached claim’s right to lodge an application in subject matter of the exclusion of an item or the right in property rights from execution. The author stressed that — due to provisions of the Act on the Administrative Enforcement Proceedings — the debtor of the attached claim has at his disposal different legal means such as, especially, a right to lodge acomplaint serving as instruments of countering the attachement of claim or property rights in case the enforcement authority does not have legal grounds for it; additionaly, she noticed that the scope of legal protection offered to the debtor of the attached claim in administrative enforcement proceedings properly secures his legal status.
Keywords: egzekucja administracyjna; dłużnik zagrożonych wierzytelności; zakres ochrony prawnej; skarga; postępowanie administracyjne